Hubungan Kreativitas Gerak & Kecerdasan Emosional dengan Hasil Belajar Eksplorasi Gerak Pada Siswa Kelas XI SMA Negeri 5 Kota Tangerang - Syifa Nurazizah, Nanda (Jurnal Pendidikan Tari, 2024)
This study examines the problem of the less optimal learning outcomes of motion exploration whether it is related to several aspects, namely motion creativity and emotional intelligence. This study aims to measure the relationship between Motion Creativity and Emotional Intelligence with Motion Exploration Learning Outcomes in Class XI Students of SMAN 5 Tangerang City. This study uses quantitative research methods with correlation techniques, data collection techniques with a total sample of 65 students. The data collection technique used a performance test for the Variables of Motion Creativity and Movement Exploration Learning Outcomes, and a non-test in the form of a questionnaire for the variable of emotional intelligence. The results of this study indicate that it is concluded that there is a relationship between the variables x1 and x2 simultaneously with the variable y. The contribution of the relationship between the variables x1 and x2 simultaneously with the variable y is 90.6%.